REFERENCES OF DISCOURSE AND ITS TYPES IN AKSHATA MURTHY: UK™S FIRST LADY SPEECH - Manurung, Siti Tasya Jelita (LINGUISTIK TERAPAN, 2023)
This study examined the references used in Akshata Murthy's speech "Best Friend," focusing on the types of references and their realization. References in communication are very important and have a great role to play in conveying the speaker's message. This study provides a theoretical framework on reference in speech and emphasis the importance of reference in effective communication. The research methodology involves descriptive qualitative analysis, with data collection through browsing, watching, copying, selecting, and underlying relevant sentences. The research found that there are many anaphoric references in the speech, which play a role in creating cohesion and coherence. The results contribute to the field of linguistics by providing an understanding of the types of reference and their significance in communication. The analysis of Akshata Murthy's speech revealed the use of various types of references, including personal, comparative, and demonstrative references, to create cohesion and coherence. Anaphoric and cataphoric references were effectively used to connect ideas and maintain the flow of the speech. Recommendations for future research include comparing referencing in speeches by different speakers and exploring the impact of figures of speech on audience comprehension and engagement. This research also has practical implications in the understanding of reference in discourse. Overall, this research thoroughly examines the analysis of references in Akshata Murthy's speeches, shedding light on the types of references employed and their manifestations. The research underscores the importance of reference in effective communication and provides insights into the utilization of diverse reference types in establishing cohesion and coherence in speech.